Missionaries and Female Empowerment in Colonial Uganda: New Evidence from Protestant Marriage Registers, 1880-1945 - Felix Meier zu Selhausen (African Economic History Network (AEHN), 2014)
Protestant missionaries have recently been praised for their comparatively benign features concerning female education in Africa. Using a new dataset of 5,212 Protestant brides born between 1880 and 1945 from urban and rural Uganda, this paper offers a first pass at analyzing empirically the role of mission education on African women's socio-economic position within the household. The paper finds that although, mission education raised the sampled brides' literacy skills way above female national levels, they were largely excluded from participating in the colonial wage labour market. In this context, the missionary society presented an almost exclusive source of female wage labour in areas of religious service, schooling and medical care. While literacy per se did not affect women's marriage behaviour, women who worked for the missionaries married significantly later in life and married men closer to their own age, signaling a shift in the power balance between parents and daughters and between husband and wife. On average, daughters of fathers deeply entrenched in the missionary movement had the highest chances to access wage employment, emphasizing the importance of paternal mission networks for Protestant women's work outside the household during colonial times.
Keywords: J12; J16; N37; N97; Z12; 330; African women; colonial economy; education; marriage patterns; Missions; Protestantism; Uganda; wage labour